Preliminary results of computer‐based multimodal training in Alzheimer's disease over six months – the multimodAAL study. (20th December 2022) - Berger, Martin; Schüssler, Sandra; Zuschnegg, Julia; Russegger, Silvia; Paletta, Lucas; Fellner, Maria; Strobl, Bernhard; Ploder, Karin; Hofmarcher‐Holzhacker, Maria; Stögerer‐Oberschmid, Eva Maria; Guttmann‐Lattmanig, Alexandra; Koini, Marisa
Abstract: Background: Alzheimer's disease (AD) is associated with cognitive decline and limited therapeutic interventions to maintain cognitive function. The present study investigates the effectiveness of a computer‐based cognitive and physical training (CCPT) on a tablet device in patients with AD and aims to present preliminary results of the multimodAAL project (project number: FFG 875345). Method: Twenty‐three patients were randomly assigned to intervention and control group (randomized controlled trial). The intervention group received weekly multimodal CCPT with a trainer and were encouraged to train as often as possible alone or with a caregiver over six months. At the time of data analysis 14 subjects had a 6‐month follow‐up with comprehensive pre and post neuropsychological assessment including tests on global cognitive functions (Mini Mental Status Examination, MMSE), memory, working memory, executive function and verbal fluency. Repeated measures ANOVA comparing neuropsychological test performance over time was calculated to determine the between‐group difference. Analyses were corrected for disease duration. Paired t‐test was used for post‐test analyses. Result: In this preliminary analysis six subjects from the intervention group (4 female, age: x̅ = 75.4, disease duration: x̅ = 30.3 months) and eight subjects from the control group (7 female, age: x̅ = 74.8, disease duration: x̅ = 30.75 months) were included. The results showed a significant interaction effect considering global cognition and group with a high effect size (MMSE: F(1, 11) = 7.503, p = 0.019, ηp 2 = 0.405). Post‐tests revealed a maintenance of performance in the intervention group (+0.68 points in the MMSE over 6 months, t(5) = ‐1.2, p = 0.300) and a significant decrease in the performance of the control group (‐1.34 points in the MMSE over 6 months; t(7) = 2.5, p = 0.041). The other cognitive domains did not show significant results. Conclusion: These preliminary results indicate that CCPT over six months has the potential to maintain global cognitive functions in Alzheimer patients.